Alterações espaciais na bacia hidrográfica do Rio Coruripe, Alagoas - Santos, Lionaldo dos (2018)
The use of the soil and vegetable coating in geographic space is constantly changing due to social, economic and political factors. The geotechnologies, as the remote sensing, are essential in studies of use of the soil and vegetable coating. The present work objected to analyze the spatial changes and socio-environmental impacts that occurred in the period 1987 to 2016, at the hydrografic basin of the Coruripe River, Alagoas. Were used Landsat-5 satellite images corresponding to the year 1987 and Landsat-8 for the year 2016. Was performed images treatment, as the realization of the composition RGB and georeferencing. The hydrografic basin was divided into two Segments for supervised classification, this division being essential to discriminate equal features with different spectral responses. To check the level of reliability of the supervised classification the Kappa concordance index was used. Segment I has extension of 515 km2 and segment II 1.179 km2 totaling an area of 1.694 km2 . Thorough supervised classification for each segment and season were determined the classes of use of the soil and vegetable coating, possible to be viewed by the Landsat-5 and 8 satellites. Was also used, as an aid for interpretation of features in the basin area, ID key, how color, texture and roughness. With the georeferenced areas, classified and vectorized, it was the measurements of the respective classes to obtain the predomint classes in 1987 and 2016. To identify socio-environmental impacts was made adaptation of Leopold Matrix, where information was crossed referring the impacting activities and their changes in the physical environment, biotic and anthropic. The classes of use of the soil and vegetable coating found in the in the hydrografic basin of the Coruripe River, Alagoas, were pasture, sugar cane, subsistence crops( pineapple, manioc, pine cone), soil exposed, vegetation, caponier, water bodies and urban area,with featured for as predominant in the studied years. According to the Kappa concordance index, the geotechnologies are satisfactory in the process of mapping segments I and II of the hydrographic basin of the Coruripe River, Alagoas in the years 1987 and 2016. The spatial changes in the hydrografic basin of the Coruripe River, occurred in virtue the diversity of farming activities and increase in urban areas. The main socio-environmental impacts identified in the hydrografic basin of the Coruripe River are domestic and industrial waste launched in water course, reduction of riparian forest in the main rivers that makes up the said basin, extensive creation of animals aroud of the source of the river Coruripe with intense eutrophication process in some parts of the rivers.